The field measurement of wellhead anti-freezing technology using exhaust wind waste heat - SUN Meng; JIANG Guanjun; FENG Jizhe; MA Tianze; ZHOU Lin (Shenzhen Daxue xuebao. Ligong ban)
A new type of directly heat transfer technology between exhaust wind and fresh air was proposed and put into practice in Shenhua Ningxia Coal Industry Group Co. Ltd. so as to solve the problems of wellhead anti-freezing, energy saving and emission reduction in hot-summer-cold-winter region, cold region and severe cold region in winter. The field measurement results show that after heated and transported to the wellhead, the fresh air is mixed with some outdoor fresh air, and its temperature is not less than 2 ℃, which meets the requirements of coal mine specifications; the latent heat in the exhaust wind is fully absorbed through droplet condensation, and the heat transfer process does not need additional energy, but only the fresh air needs power. The average coefficient of performance (ratio of heating capacity to input power) in a heating period reaches 12.1, by replacing the original 2.0×104 kg of coal-fired boilers with new technology, the emissions of 1.881×107 kg carbon dioxide, 4.8×104 kg nitrogen oxides, 4.8×104 kg of sulfur dioxide, and 2.178×104 kg of dust directly, which used to be discharged into the atmosphere by mine exhaust wind, will be reduced annually. The operating cost of the system is only 2.258 5 million Yuan per heating season, saving 4.266 5 million Yuan compared with the natural gas boiler system and 7.998 1 million Yuan compared with the coal-fired boiler system. The use of wall type exhaust wind and fresh air direct heat transfer technology has low operation cost, and it has no pollution of waste water, waste gas and waste residue in the operation process. It is a green environmental protection, high efficiency and energy saving technology, and can provide technical support for the construction of new modern and green mine.